Determinação de resíduos de glifosato e ácido aminometilfosfônico em água empregando derivatização com FMOC-Cl e LC-MS/MS - Reinke, Karine (2020)
A simple and easy method based on the derivatization for determinação of glyphosate and aminomethylphosphonic acid (AMPA) in water and subsequent determination by liquid chromatography coupled with mass spectrometry in series (LC-MS/MS) was evaluated. Intrinsic parameters of the derivatization technique, such as derivatization time, derivatizer volume, cleaning solution volume and composition were investigated in order to ensure the best performance of the proposed method. In addition, two methods of preparing the analytical curve were evaluated: 1) prepare the points of the curve individually (derivatized curve) and 2) derivatize a point of high concentration and prepare the curve from its dilutions in water (diluted curve). The stability of glyphosate and AMPA in derivatized solutions were evaluated at room temperature (15-25 °C) and under refrigeration (<10 ° C) for 28 days. The ideal experimental condition consisted of 30 min of privatization of 2 ml of water with 3 ml of 9-fluorenylmethyl chloroformate (FMOC-Cl). 6 mL of ethyl acetate was used as a cleaning solvent because it is more efficient at removing interferents, in addition to being an environmentally friendly solvent when compared to dichloromethane. The analytical curves were prepared from dilutions of a derivatized standard solution of 100 μg L-1 and presented linearity of 0.5 to 20 μg L-1. The accuracy and intermediate precision were 79 to 119% and RSD < 20%, in water of tap and river, with no matrix effect (<±20%). The qualification limits (LOQ) for glyphosate and AMPA were 0.5 μg L-1. After validation, the method was applied to 38 samples from cities in states of Rio Grande do Sul and Mato Grosso (Brazil), with four positive samples for glyphosate and one for AMPA. The proposed method proved to be an adequate tool for monitoring glyphosate and AMPA in water samples.